Virtual cockpit instrumentation using helmet mounted display technology - Lueken, T.; Ernst, J.M.; Doehler, H.-U. (My University, 2015)
DLR's Institute of Flight Guidance has developed a new concept for virtual cockpit instrumentation based on a monochrome green "looking-through" helmet mounted display system (JedEye™). The resolution of the helmet is more than HD-TV, good enough to show detailed information as on presently installed head-down instruments. In addition to our latest 3D helicopter landing symbology, basic virtual instruments like Primary Flight Display, Navigation Display, and knee-board have been implemented in the near field of the cockpit environment in "no-window" areas. Pilots perceive these display elements as if they were located within the cockpit structure at a fixed and stable location in space. Besides, we have realized a "drag and drop" mechanism, which enables pilots to interactively arrange instrumentation on their personal preference by moving the display to another location, and additionally to adapt the display size. To prevent the pilot from dealing with too many different buttons, the interface comprises only three push buttons, which can easily be configured to be driven by already existing buttons on collective or center stick. The employment of only three push buttons and the pilot's head movements tries to make the mechanism intuitive and straightforward. First pilots' feedback show, our concept offers a great potential to be introduced into the future flight deck. This paper describes the implementation of both the helmet based virtual cockpit instrumentation in combination with a visual-conformal landing display format and the HMI concept with the usage of a high sophisticated helmet mounted display system.
Keywords: Aircraft Systems, Avionics & Sensors